English is not useful for my afterlife: Teachers and students perspectives of English language teaching in pesantren - Mustofa, Mutmainnah; Romadhon, M Galuh Elga (Universitas Syiah Kuala, 2025)
This study investigates the core beliefs of English teachers facilitating English language learning in Islamic boarding schools. Using a phenomenological research method, the research explores the lived experiences of six participants, four students (S1, S2, S3, S4) and two teachers (T1, T2), regarding English learning in Islamic educational settings. The study conducted detailed, semi-structured interviews and observations at a privately-run Islamic boarding school in Pasuruan regency, East Java, Indonesia. The results reveal that the teachers face significant challenges including inadequate technological resources, poor student motivation, and beliefs that religious knowledge supersedes English proficiency. Likewise, the students initially demonstrated low motivation due to limited extracurricular activities and perceptions that English conflicts with religious studies. However, institutional interventions through interactive techniques, modern teaching practices, and cultural exchange programs gradually improved student attitudes. Adaptive strategies emerged, incorporating Islamic values into language education while emphasizing Englishs practical applications. The findings suggest that culturally sensitive and innovative teaching strategies are crucial for effective English language acquisition in religious educational settings. By integrating Islamic principles into language instruction, educators can enhance student engagement while preserving cultural identity. This study provides important perspectives on English language learning in Islamic boarding schools and presents recommendations for educators and policymakers to enhance language education in similar contexts, while maintaining respect for religious and cultural values.